미만성 갑상샘 질환에서 GLCM을 이용한 초음파 영상 분석 - 예수영; Soo-young Ye (한국방사선학회 논문지, 2021)
미만성 갑상샘질환은 그 진단 기준이 모호하고 숙련자의 주관적인 진단에 따라 오류가 많이 발생한다. 또한 갑상샘 결절의 초음파 영상에 관한 연구는 활발히 이루어졌지만 미만성 갑상샘질환에 관한 연구 사례는 미흡한 실정이다. 본 연구에서는 정상과 미만성 갑상샘질환의 영상에 GLCM 알고리즘을 적용하여 영상의 특징을 추출하고 추출된 특징값을 파라미터를 이용하여 정량적인 분석을 하였다. W 병원에서 진단한 환자의 갑상샘 초음파 영상을 대상으로 GLCM 알고리즘을 이용하여 정상 199증례, 경도 132증례, 중등도 99증례 총 영상 430증례에 관심영역(50x50 pixel)을 설정하고, 각 영상에서 Autocorrelation, Sum of squares, Sum average, Sum variance, Cluster prominence, Energy 6가지 파라미터를 이용하여 분석하였다. Autocorrelation, Sum of squares, Sum average, Sum variance 4가지 파라미터에서 Normal, Mild, Moderate를 구분하는데 90%이상의 높은 인식률을 보였다. 미만성 갑상샙질환의 초음파영상에서 GLCM 알고리즘을 이용하여 미만성 갑상샘질환의 심각도 정도를 분류하는 기준으로서 가치가 있다. 이러한 파라미터를 적용하여 갑상샘질환의 진단에 있어 육안 판독에 따른 오류를 감소시키고 미만성 갑상샘질환 진단의 2차적인 수단으로 활용 가능할 것으로 기대된다. The diagnostic criteria for diffuse thyroid disease are ambiguous and there are many errors due to the subjective diagnosis of experts. Also, studies on ultrasound imaging of thyroid nodules have been actively conducted, but studies on diffuse thyroid disease are insufficient. In this study, features were extracted by applying the GLCM algorithm to ultrasound images of normal and diffuse thyroid disease, and quantitative analysis was performed using the extracted feature values. Using the GLCM algorithm for thyroid ultrasound images of patients diagnosed at W hospital, 199 normal cases, 132 mild cases, and 99 moderate cases, a region of interest (50x50 pixel) was set for a total of 430 images, and Autocorrelation, Sum of squares, sum average, sum variance, cluster prominence, and energy were analyzed using six parameters. As a result, in autocorrelation, sum of squares, sum average, and sum variance four parameters, Normal, Mild, and Moderate were distinguished with a high recognition rate of over 90%. This study is valuable as a criterion for classifying the severity of diffuse thyroid disease in ultrasound images using the GLCM algorithm. By applying these parameters, it is expected that errors due to visual reading can be reduced in the diagnosis of thyroid disease and can be utilized as a secondary means of diagnosing diffuse thyroid disease.